1991
DOI: 10.1083/jcb.114.3.545
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of connexin 43-mediated gap junctional intercellular communication by Ca2+ in mouse epidermal cells is controlled by E-cadherin.

Abstract: Abstract. Gap junctional intercellular communication (GJIC) of cultured mouse epidermal cells is mediated by a gap junction protein, connexin 43, and is dependent on the calcium concentration in the medium, with higher GJIC in a high-calcium (1.2 mM) medium . In several mouse epidermal cell lines, we found a good correlation between the level of GJIC and that of immunohistochemical staining of E-cadherin, a calciumdependent cell adhesion molecule, at cell-cell contact areas. The variant cell line P3/22 showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
151
1
6

Year Published

1992
1992
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(165 citation statements)
references
References 48 publications
7
151
1
6
Order By: Relevance
“…More recently, Musil and Goodenough (1991) showed that cx43 in the triton-insoluble fraction, which represents cx43 in the gap junctional plaques, exists mainly in the phosphorylated P2 form and that the phosphorylation takes place after cx43 incorporation into the (nonjunctional) membrane. This implies that (Loewenstein, 1967;Keane et al, 1988;Mege et al, 1988;Musil et al, 1990;Jongen et al, 1991).…”
Section: Discussionmentioning
confidence: 96%
“…More recently, Musil and Goodenough (1991) showed that cx43 in the triton-insoluble fraction, which represents cx43 in the gap junctional plaques, exists mainly in the phosphorylated P2 form and that the phosphorylation takes place after cx43 incorporation into the (nonjunctional) membrane. This implies that (Loewenstein, 1967;Keane et al, 1988;Mege et al, 1988;Musil et al, 1990;Jongen et al, 1991).…”
Section: Discussionmentioning
confidence: 96%
“…Alternatively, the presence of low levels of ZO-1 at the edge of Cx43-GFP plaques could result indirectly via macromolecular associations between GJs and other cell-cell junctions that incorporate ZO-1. Adherens junctions are logical candidates in this respect as they are known to play a pivotal role in GJ stability (Hertig et al 1996;Jongen et al 1991;Li et al 2005;Meyer et al 1992;Musil et al 1990;Wei et al 2005) and cadherin-associated catenin complexes have been shown to bind both Cx43 (Ai et al 2000;Wei et al 2005) and ZO-1 (Itoh et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the overall expression and distribution of Ecadherin (Fig. 6), which has been suggested to play a role in Cx43 assembly, perhaps by providing cell-cell adhesion necessary for gap junction formation, [28][29][30][31][32] does not differ between the parental and mutant cell types. Thus, as for transport proteins whose trafficking is altered in Trf1 cells, it appears as though connexin trafficking, but not that of E-cadherin, is affected.…”
Section: Discussionmentioning
confidence: 99%